2018
DOI: 10.3851/imp3330
|View full text |Cite
|
Sign up to set email alerts
|

Boosted Darunavir and Dolutegravir Dual Therapy among a Cohort of Highly Treatment-Experienced Individuals

Abstract: Background: The use of dual antiretroviral therapy (ART) regimens for treatment of HIV is increasing. The contemporary combination of boosted darunavir with dolutegravir has not been widely studied. Methods: This was a retrospective cohort study that evaluated treatment-experienced individuals within three large urban clinics prescribed boosted darunavir with dolutegravir (study regimen) dual therapy. Follow-up was defined as the number of days from regimen initiation until the last HIV RNA determination on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Despite the limited sample size, the randomized DUALIS study showed that switching to DTG + bDRV was non-inferior to continuing boosted DRV plus two NRTIs [11]. Likewise, the efficacy of DTG + bDRV reported in other observational studies among viraemic patients was promising [12,13,15,17], confirming the attractiveness of this option. However, despite this high efficacy, our results showed that patients receiving a non-fully active regimen showed a lower probability of VS (80.0%), suggesting that careful review of GRT results must also be considered.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Despite the limited sample size, the randomized DUALIS study showed that switching to DTG + bDRV was non-inferior to continuing boosted DRV plus two NRTIs [11]. Likewise, the efficacy of DTG + bDRV reported in other observational studies among viraemic patients was promising [12,13,15,17], confirming the attractiveness of this option. However, despite this high efficacy, our results showed that patients receiving a non-fully active regimen showed a lower probability of VS (80.0%), suggesting that careful review of GRT results must also be considered.…”
Section: Discussionmentioning
confidence: 86%
“…Nowadays, DTG + bDRV regimen is mainly prescribed in highly treatment-experienced patients and with high prevalence of MRMs, not only in the NRTI class, but also in the PI class [12,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-word data are in line with the results of this study. Several cohort studies evaluating bDRV plus DTG in PLWH with extended treatment experience and an even higher prevalence of NRTI, NNRTI, and major PI RAMs than in the DUALIS study confirmed a high virologic effectiveness and a high resistance barrier of the dual regimen [12][13][14][15]. In a small retrospective cohort study, 49 of 50 PLWH (98%) maintained viral suppression on bDRV and DTG for a median of 25 months without the emergence of new RAMs [14].…”
Section: Discussionmentioning
confidence: 93%
“…In the present work, we designed, synthesized, and identified two novel nonpeptidic HIV-1 protease inhibitors (PIs), GRL-037 and GRL-044, containing (i) P2-tetrahydropyrano-tetrahydrofuran (Tp-THF), (ii) P1-benzene and P1-methoxybenzene, respectively, and (iii) P2'-isopropyl-aminobenzothiazole (Ip-Abt) on the structure of darunavir (DRV) (7,8), which is the last approved PI for the treatment of HIV-1 infection/AIDS and has been most used worldwide (8)(9)(10). Both GRL-037 and GRL-044 showed potent antiviral activity against wild-type HIV-1, but GRL-044, in particular, exerted potent antiviral activity against wild-type HIV-1, HIV-2, and various drug-resistant HIV-1 variants.…”
Section: Introductionmentioning
confidence: 99%